Cognitive and Psychological Outcomes Following Pediatric Cardiac Arrest - Huebschmann, Nathan A.; Cook, Nathan E.; Murphy, Sarah; Iverson, Grant L. (Frontiers in Pediatrics, 2022)
Cardiac arrest is a rare event in children and adolescents. Those who survive may experience a range of outcomes, from good functional recovery to severe and permanent disability. Many children experience long-term cognitive impairment, including deficits in attention, language, memory, and executive functioning. Deficits in adaptive behavior, such as motor functioning, communication, and daily living skills, have also been reported. These children have a wide range of neurological outcomes, with some experiencing specific deficits such as aphasia, apraxia, and sensorimotor deficits. Some children may experience emotional and psychological difficulties, although many do not, and more research is needed in this area. The burden of pediatric cardiac arrest on the child’s family and caregivers can be substantial. This narrative review summarizes current research regarding the cognitive and psychological outcomes following pediatric cardiac arrest, identifies areas for future research, and discusses the needs of these children for rehabilitation services and academic accommodations.